In vitro Antioxidant, Antifungal and Antibacterial Activities of Essential Oil of Morina longifolia Wall. Leaves (2014)
Essential oil isolated from the leaves of Morina longifolia, a perennial aromatic herb of medicinal value distributed in the temperate and alpine region of the Himalayas from Kashmir to Bhutan, was screened for in vitro antioxidant, antifungal and antibacterial activities. Compared to the reference antioxidant compounds, the oil showed antioxidant capacity comparable to BHT and α-tocopherol and higher than BHA in Oxygen Radical Absorbance Capacity (ORAC) assay. The oil exhibited pronounced antifungal and varied antibacterial activities against four fungi (Alternaria alternata, Aspergillus flavus, A. fumigatus and Fusarium solani) and six bacteria (Escherichia coli, Staphylococcus aureus, Proteus vulgaris, Klebsiella pneumonia, Bacillus subtilis and Pseudomonas aeruginosa determined using spore germination and disc diffusion method, respectively. The inhibitory activity of the oil in Gram positive bacteria was higher than the Gram negative bacteria. Our findings indicate that the essential oil isolated from M. longifolia leaves could be used as an antioxidant and antimicrobial agent in food, pharmaceutical and pesticide industries.